Influence of sodicity on cation composition, growth, yield and quality of chilli (Capsicum annuum L.) - Garg, V K (Journal of Spices and Aromatic Crops, 2009)
Field trials conducted at Lucknow (Uttar Pradesh) to study the performance of chilli(Capsicum annuum) in sodic soil with four genotypes (Jwala, PC-1, KDCS-810 and LCA-235) and five levels of exchangeable sodium percentage (ESP) (10, 20, 30, 40 and 50) indicatedthe adverse effect of sodicity and hence picking of red ripe fruits may be stopped after thesixth one when there is about 25% reduction in fruit size. Maximum mean yield (fresh) wasobtained in LCA-235 (16.2 t ha-1) followed by KDCS-810 (13.1 t ha-1), PC-1 (12.0 t ha-1) andJwala (10.3 t ha-1). There was less reduction in yield of LCA-235 and KDCS-810 than Jwalaand PC-1 at higher sodicity level (ESP=40) revealing greater sodicity tolerance. Cationcomposition of different plant parts indicated salt (Na) exclusion mechanism and higher K/Na and Ca/Na ratio supporting the potential of chilli crop to endure greater degree of sodicity.Physical fruit quality with respect to length, diameter and pod weight were affected by soilsodicity and decreased with increase in soil sodicity. Oleoresin and capsaicin contents didnot vary with increase in sodicity, whereas, ascorbic acid content was reduced.